Maintaining and Improving the Audit Competence of CPAs: CPA and Selected User Reaction. - Kreiser, Larry (The Accounting Review, 1977)
Abstract ABSTRACT: A certificate or license defining professional status implies that the holder has a certain minimum level of professional competence. Until recently, little attention has been directed by the public accounting profession toward whether a CPA maintains professional competence throughout his or her career. This study was designed to accomplish two objectives: (1) to measure the reaction of CPAs and users of CRA services to the structure of programs for upgrading CPA audit competence and (2) to measure CPA and user reaction to the effectiveness of eight specific competence-upgrading programs. Empirical evidence needed to answer the two objectives was collected by a mailed questionnaire sent to selected members of the American Institute of Certified Public Accountants, Financial Executives Institute, Institute of Chartered Financial Analysts and Robert Morris Associates. All responses were examined for statistically significant differences in the distribution of responses within and between groups. The empirical evidence collected in this study indicated a significant difference in the frequency of expressed opinion between CPAs and users of CPA services regarding the most effective, and also the least effective, competence-upgrading program. Additional research evidence was collected which dealt with the structure of competence-upgrading programs.